The contribution of academic Nursing monitoring in clinical surgery on the student-monitor perspective (Research, Society and Development, 2020)
Objective: To report experiences of nursing academics in the performance of their mentoring activities of the curricular component "Nursing in Surgical Clinics", describing contributions and work developed by monitors at a Public University of Northern Brazil. Methods: This is a qualitative and descriptive study, of the experience report type, developed from the experience of students during the monitoring of the curricular component "Nursing in Surgical Clinics", which, in the undergraduation in Nursing, is offered to the 5th semester students, totalizing 200 hours of the semester load. The mentoring is divided into theoretical and practical classes. Results: It was possible to establish a greater approximation with the contents taught and obtained in the graduation course in nursing, since it is necessary to appropriate the contents and seek updates in the available literature in order to take advantage of the best possible experience that monitoring has to offer. Conclusions: The academic mentoring, stimulates the scientific and technical knowledge improvement of the student-monitor, offering him or her several clinical experiences, such as leadership in group studies, rehearsals to teaching and improvement of techniques performed in hospital practices.